Administrative Law Discipline Measures for Civil Servants in Musi Rawas Regency - Larasati Khoirunnisa; Sunarno (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The success of the government program and national development depend primarily on the perfection of the state apparatus and in essence depends on civil servants. To achieve full dedication of the civil servants, they need to be well nurtured in accordance with to achieve full dedication of the civil servants, they need to be well nurtured in accordance with Pancasila and the 1945 Constitution. Discipline behavior of employees as servants of the state should be applied properly so that the administration of government can run smoothly, effectively, and efficiently. How is the implementation of disciplinary action for civil servants in Musi Rawas Regency, what factors cause dishonored dismissal of the civil servants, and what factors hinder disciplinary action for civil servant in the regency are among the problems discussed in this study. The purpose of the study is to reveal the causes of indiscipline and to find out the restriction of punishment. This paper belongs to normative and empirical legal research as the data were gathered through normative law and literature with statute and comparative approaches. How is the implementation of disciplinary action for civil servants in Musi Rawas Regency, what factors cause dishonored dismissal of the civil servants, and what factors hinder disciplinary action for civil servant in the regency are among the problems discussed in this study.